2011
DOI: 10.1371/journal.pone.0026927
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Artificial Selection on Ambulatory Dispersal Distance in Tetranychus urticae: Effects of Density and Maternal Effects

Abstract: Dispersal distance is understudied although the evolution of dispersal distance affects the distribution of genetic diversity through space. Using the two-spotted spider mite, Tetranychus urticae, we tested the conditions under which dispersal distance could evolve. To this aim, we performed artificial selection based on dispersal distance by choosing 40 individuals (out of 150) that settled furthest from the home patch (high dispersal, HDIS) and 40 individuals that remained close to the home patch (low disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 69 publications
1
39
2
Order By: Relevance
“…After hatching and juvenile development, 50 one-to-two-day old mated females were chosen at random to start the dispersal procedure. These young T. urticae females are the dominant dispersers (Bitume et al 2011). The dispersal procedure was initiated by translocating the females to a bean leaf square that subsequently served as the source population for dispersal (1 3 1 cm, in order to generate sufficiently high densities that induce emigration; see Bitume et al 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After hatching and juvenile development, 50 one-to-two-day old mated females were chosen at random to start the dispersal procedure. These young T. urticae females are the dominant dispersers (Bitume et al 2011). The dispersal procedure was initiated by translocating the females to a bean leaf square that subsequently served as the source population for dispersal (1 3 1 cm, in order to generate sufficiently high densities that induce emigration; see Bitume et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the unusual nature of these mutations, these resistant mites do not differ in life history traits relative to those from the baseline strain from which they have been selected (Van Leeuwen et al 2008). In Tetranychus urticae, density and relatedness act as proximate drivers of dispersal distance (Bitume et al 2013), and dispersal distance heritability is strongly influenced by the prevailing densities (Bitume et al 2011). The distribution of individuals after dispersal is typically right, skewed with more individuals settling at smaller distances, and deviates significantly from a homogenous distribution, i.e., the ideal free distribution (Fretwell and Lucas 1970, Fretwell 1972, Krivan et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For the host plant change experiment, we transferred 1-to 3-d-old females (London strain) from their common host, Phaseolus vulgaris (kidney beans), to a more challenging and less accepted host, Solanum lycopersicum (tomato). We used young females because at this stage they actively disperse with the wind to escape kin competition and overexploitation (39,40) and hence are expected to encounter potentially less favorable plants, on which they must immediately feed to produce eggs for colony establishment (colonies can then persist for many generations). We followed transcriptional changes over the short term to understand the initial responses, as well as after five generations on the new host.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the many studies that have investigated traits associated with dispersal between core and range edge populations, and dispersal syndromes within a population, manipulative experiments that investigate trait evolution under selection for dispersal are relatively uncommon (Yano & Takafuji 2002;Friedenberg 2003;Łomnicki 2006;Bitume et al 2011;Fronhofer & Altermatt 2015;Van Petegem et al 2015). These types of studies are imperative to bridge the divide between studies within and among populations, by allowing evolutionary processes to be observed in real time, and under controlled conditions (Kawecki et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Van Petegem et al 2015) or life-history traits (e.g. Bitume et al 2011), but typically not morphology (but see Łomnicki 2006), physiology, or behaviour. These functional, phenotypic traits are hypothesised to be crucial components of dispersal syndromes, and undoubtedly contribute to movement ability.…”
Section: Introductionmentioning
confidence: 99%